Which radiograph is most accurate for assessing hip joint penetration in infra-acetabular screw placement?. Issue 24 (18th June 2021) - Lim, Eic Ju; Sakong, Seungyeob; Choi, Wonseok; Oh, Jong-Keon; Cho, Jae-Woo
Abstract : Abstract: Although infra-acetabular screws have been used for anterior and posterior column transfixation, a screw penetrating the hip joint can result in harmful complications. However, the most accurate intraoperative radiologic imaging tool for identifying articular penetration has not been established. The purpose of the present study was, therefore, to evaluate the consistency with which standard pelvic radiographs compared with computed tomography (CT) can be used for demonstrating articular penetration. This retrospective review was performed between January 2015 and December 2020. We evaluated the records of patients with acetabular or pelvic fractures who underwent open reduction and internal fixation with infra-acetabular screw placement. We collected demographic data and described infra-acetabular screw placement as follows: ideal placement, articular penetration, and out of the bone. Articular penetration was assessed independently on each pelvic radiograph and compared statistically with the CT scans. Sensitivity, specificity, correct interpretation rate, and prevalence-adjusted bias-adjusted kappa (PABAK) were calculated for each radiograph. Thirty-nine patients underwent infra-acetabular screw placement. The mean age of patients was 55 years (range, 27–90 years); there were 29 men and 10 women. One patient underwent bilateral infra-acetabular screw placement; therefore, 40 infra-acetabular screws were included in total. Six (6/40, 15%) infra-acetabular screws showed articular penetration on CT and two (2/40, 5%) showed infra-acetabular screws extending out of the bone. Hip joint penetration was correctly identified at a rate of 92.5% (95% confidence interval [CI], 79.6–98.4%) on the outlet view and 87.5% (95% CI, 73.2–95.8%) on the anteroposterior (AP) view. The PABAK for the agreement between pelvic radiographs and CT scans was 0.85 in the outlet view and 0.75 in the AP view. The outlet view is an accurate method for detecting articular penetration of infra-acetabular screws. We recommend the insertion of an infra-acetabular screw under fluoroscopic outlet view to avoid articular penetration intraoperatively.